2013
DOI: 10.3329/bjvm.v10i1-2.15652
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effect of Ginger Extract in Vanaspati Fed Rats

Abstract: The aim of the present study was to evaluate the hypolipidemic effect of ginger in vanaspati fed rats. A total of 18 rats of Long Evans strain weighing 200-250 g were randomly assigned to three groups: Group I, normal control; Group II, 5% vanaspati supplement and Group III, 5% vanaspati + ginger extract (300 mg/ 100ml/ kg b. wt./ day) orally. Serum lipid profile was measured at day 1st and day 49th. The administration of vanaspati augmented the total cholesterol, LDL-C, triglycerides levels and decreased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…GR constituents also alleviate TC levels via another reported mechanism of upgrading hepatic cholesterol 7α-hydroxylase activity. This is a rate-limiting enzyme in the conversion of serum free cholesterol to bile acids and downregulating HMGR genes (responsible for encoding rate-limiting enzymes in cholesterol biosynthesis), hence lowering serum TC and the risk of coronary heart disease [48,51]. Remarkably reduced levels ( p < 0.05) of vLDL-C, LDL-C, and triglycerides and elevated levels of HDL-C can be explained by the presence of niacin in GR extracts.…”
Section: Discussionmentioning
confidence: 99%
“…GR constituents also alleviate TC levels via another reported mechanism of upgrading hepatic cholesterol 7α-hydroxylase activity. This is a rate-limiting enzyme in the conversion of serum free cholesterol to bile acids and downregulating HMGR genes (responsible for encoding rate-limiting enzymes in cholesterol biosynthesis), hence lowering serum TC and the risk of coronary heart disease [48,51]. Remarkably reduced levels ( p < 0.05) of vLDL-C, LDL-C, and triglycerides and elevated levels of HDL-C can be explained by the presence of niacin in GR extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Paul et al, 2012 confirmed that it has hypolipidemic activity in animal experiment [9]. Srivastava and Mustafa (1992) proved that it is useful for rheumatism and musculoskeletal disorders through clinical trials [10].…”
Section: Introductionmentioning
confidence: 89%
“…These distinct properties prevent development of atherosclerosis. [25][26][27][28][29][30][31][32][33][34][35][36]…”
Section: Prevention Of Atherosclerosismentioning
confidence: 99%